Evaluation of Two Automated Methods for Measurement of the Ristocetin Cofactor Activity of von Willebrand Factor - Miller, Connie H.; Platt, S. Jean; Daniele, Christine; Kaczor, Daniel (Thrombosis and Haemostasis, 2002)
We have evaluated two automated methods for measuring ristocetin cofactor activity (VWF:RCo) on an automated coagulation analyzer (STAR®, Diagnostica Stago Inc., Parsippany, NJ). A modification of the BC von Willebrand Reagent method (Dade Behring Inc., Newark, Delaware) was compared with a standard method using a platelet aggregometer, and an in-house automated method was developed using commercially available components. The STAR® measures the change in optical density (OD) caused by agglutination of platelets. Change in OD was linear for plasma dilutions between .25 and .04 U/mL. Coefficient of variation compared favorably with that of the standard method. In 123 normal women, the correlation coefficient (r) = .905. In menorrhagia cases, r = .901. In 20 VWD patients, r = .93. The CDC in-house method was compared to the BC Reagent method in 79 additional menorrhagia cases, with r = .94. The automated methods produced results equivalent or superior to those of traditional methods of measuring VWF:RCo.
Keywords: von Willebrand factor; ristocetin cofactor; methods